OPTIMIST-G (Optimization of Metacognitive Thinking Skills through STEAM-Based Gamification) in Chemical Bonding Learning - Ahmar, Dewi Satria; Azzajjad, Muhammad Fath (PT Mattawang Mediatama Solution, 2025)
By using a STEAM-Based Gamification method, this study seeks to maximize students' capacity for metacognitive thinking when learning chemical bonds. In the odd semester of 2023, 28 Biology Education students in class C participated in a quantitative study using a one-group pretest-posttest design. The metacognition questionnaire and the pretest-posttest were the primary tools utilized, and the paired t-test and Effect Size (Cohen's d) were employed to analyze the results. After using STEAM-Based Gamification, students' metacognitive thinking skills significantly improved, according to the results (p-value <0.05). According to the Effect Size value (Cohen's d = 2.63), this approach has a very significant impact. The learning strategy planning component saw the largest growth (+35.6%), demonstrating students' growing capacity to oversee their own learning. According to these results, STEAM-Based Gamification may be widely used to teach difficult chemical topics. By developing more interactive, reflexive, and student-centered learning experiences and enhancing their preparedness for the challenges of the Education 4.0 age, this strategy has the potential to transform the educational paradigm in the future.